ChemInform Abstract: Ambivalent Role of Metal Chlorides in Ring Opening Reactions of 2H‐Azirines: Synthesis of Imidazoles, Pyrroles and Pyrrolinones. Issue 6 (20th February 2013) - Auricchio, Sergio; Truscello, Ada M.; Lauria, Mirvana; Meille, Stefano V.
Abstract 2H‐Aziridines are applied in the reactions with imines, enaminones and enaminoesters to afford imidazoles [cf.